Orientation teachers of physical education for improve own health - Y.Y. Muskharina; V.V. Babak; Y. V. Burov; S.A. Chernobay (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Purpose . The features targeted pedagogical influence on students of the Faculty of Physical Education to strengthen their own health. Material and methods . The study involved 192 students of different pedagogical university faculties of both sexes aged 18-21 years. Results . Revealed that the level of health is not very different Arts Students from the students of the Faculty of Physical Education and is the most "below average". In the process of training future teachers of physical culture introduced pedagogical conditions : enriching the content of academic disciplines of scientific information and educational support during the implementation of the rehabilitation program students. Found that as a result of research indicators of physical health of students of physical education have improved significantly. Conclusions . These data indicate the feasibility and necessity of using these pedagogical conditions in the orientation of the future teachers of physical training to strengthen their own health and the health of the younger generation.